Educación superior e imaginarios de género (2011)
ABSTRACT: Higher education and the gender imaginaries. Robinson Restrepo García, Nora Eugenia Franco Muñoz, Ruth Elena Quiroz Posada. Gender imaginaries, the core analysis of this research, permeate actions, discourses, and relationships among people who interact in the different spaces of higher education institutions. It is there where these imaginaries are embodied in the organizational culture, which affects academic and scientific education. This study allows us to affirm this, where a discussion group was used as a working unit, and several interviews as tools for data collection. Although the topic of gender imaginaries is widely spread in much of the literature on gender, paradoxically, the information that makes specific reference to that subject in higher education, especially in the organizational culture is not very large. Such a finding, lead us to do a more generous bibliographic trace demonstrating that contrary to what it is believed, control and decision-making in higher education still remain in the hands of men. This becomes an important analysis input that challenges social researchers and administrators of higher education institutions, and calls them to think about the development of a more conscious and equitable process to be implemented this level of education.